New media facades : a global survey - Haeusler, M. Hank; Tomitsch, Martin; Tscherteu, Gernot; Berkel, Ben van, 1957- (Ludwigsburg Avedition, 2012)
New trends, directions and technologies are discussed and matching products complete this global survey of new media facades. The book is a publication of the Media Architecture Institute Vienna/Sydney and summarises their research efforts in this field over three years.
Includes bibliographical references.
Keywords: Facades -- Technological innovations; Media architecture; Architecture and technology; Exterior walls; Architecture -- Details; Communication in architecture; Lighting, Architectural and decorative; Architecture, Modern -- 21st century